2013
DOI: 10.1093/nar/gkt636
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of human P1*P2 heterodimer provides insights into the role of eukaryotic stalk in recruiting the ribosome-inactivating protein trichosanthin to the ribosome

Abstract: Lateral ribosomal stalk is responsible for binding and recruiting translation factors during protein synthesis. The eukaryotic stalk consists of one P0 protein with two copies of P1•P2 heterodimers to form a P0(P1•P2)2 pentameric P-complex. Here, we have solved the structure of full-length P1•P2 by nuclear magnetic resonance spectroscopy. P1 and P2 dimerize via their helical N-terminal domains, whereas the C-terminal tails of P1•P2 are unstructured and can extend up to ∼125 Å away from the dimerization domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
64
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 63 publications
7
64
0
Order By: Relevance
“…Because other RIPs, such as Stx1 (30,31) and TCS (29,33), also bind to the stalk to depurinate the SRL and contain basic residues at similar positions, the orientation of the active site toward the SRL by stalk binding may be a general mechanism applicable to other RIPs that interact with the stalk. Consistent with this model, recent results indicate that the level of depurination by TCS depends on the length of the hinge region within the C-terminal tail of the P-proteins (32).…”
Section: Stalk Binding Stimulates the Catalysis Of Ribosomesupporting
confidence: 57%
See 1 more Smart Citation
“…Because other RIPs, such as Stx1 (30,31) and TCS (29,33), also bind to the stalk to depurinate the SRL and contain basic residues at similar positions, the orientation of the active site toward the SRL by stalk binding may be a general mechanism applicable to other RIPs that interact with the stalk. Consistent with this model, recent results indicate that the level of depurination by TCS depends on the length of the hinge region within the C-terminal tail of the P-proteins (32).…”
Section: Stalk Binding Stimulates the Catalysis Of Ribosomesupporting
confidence: 57%
“…Previous studies showed that trichosanthin (TCS), a single chain RIP (29), and the A 1 chain of Shiga toxin 1 (Stx1) (30,31) interact with the conserved CTD fragment of P0, P1, and P2. A recent solution structure of the fulllength P1/P2 heterodimer showed a helical N-terminal domain and an unstructured C-terminal tail, which is required for the depurination activity of TCS (32). The structure of a peptide corresponding to the last 11 amino acids of the stalk proteins in a complex with TCS has been determined (33).…”
mentioning
confidence: 99%
“…Furthermore, based on our NMR structure of the stalk protein complex of P1/P2 heterodimer and biochemical analyses, we demonstrated that the flexible C-terminal tail of eukaryotic ribosome stalk can form an arm-like structure and extend with a radius up to ~125 Å [18,19,20], hinting that the complex can help recruiting RIPs towards the core of the ribosome upon RIP-P protein interaction. Apart from interacting with RIPs, several studies have reported that the conserved C-terminal motif of ribosomal P proteins is crucial for binding translation factors or interacting with elongation factors in bacterial [21,22], archaeal [11] and eukaryotic ribosomes [23].…”
Section: Introductionmentioning
confidence: 99%
“…In archaea, the ribosomal stalk is a heptamer, L10–(L12) 6 [10], whereas in eukaryotes, it is a pentamer, P0–(P1–P2) 2 [11]. Despite a wealth of crystallographic [5,1219], NMR [20,21], cryo-EM [17,22,23] and SAXS [24,25] studies, the L12/P stalk represents the last structure on the ribosome for which the architecture and precise molecular function still remain poorly established.…”
Section: Introductionmentioning
confidence: 99%